Situational analysis on porcine diseases: general risk assessment and prioritization of epizootic threats to biosecurity systems of pig establishments in the Russian Federation - A. S. Oganesyan; M. A. Shibayev; O. N. Petrova; N. Ye. Baskakova; A. K. Karaulov (Ветеринария сегодня)
The results of the situational analysis on porcine diseases in the Russian Federation and the expert assessment prioritizing the list of porcine pathogens significant for the pig industry of the country are presented. The method applied to analyse the expert estimates in the situational analysis allows for rapid assessment and interpretation of the situation with identification of priority diseases to be further addressed. The calculations demonstrated the sufficient degree of agreement among the experts (coefficient of concordance W = 0.61), and Pearson’s chi-squared test statistic χ2 = 51.33 (≥ 21.02607) indicated that the concordance is not random and the results can be used in subsequent studies. The specific features of epizootiology of the agents of African swine fever, classical swine fever, porcine reproductive and respiratory syndrome that can impact the effectiveness of biosecurity systems of pig establishments, as well as further ways for improving biosecurity management measures are discussed. The overall risk for the pig industry in the Russian Federation that is associated with external sources is currently characterized as permanently high, requiring maintaining risk management measures at the pig establishments by both the managerial staff of the establishments and the State Veterinary Service. It is recommended that biosecurity measures against external threats should focus on diseases such as African swine fever (weight λ = 0.52), porcine reproductive and respiratory syndrome (λ = 0.071), classical swine fever (λ = 0.068) and infections considered emerging for the Russian Federation (λ = 0.05) according to the weights based on the expert estimation results. The biosecurity systems of the establishments should equally address other threats significant for the pig industry of the country: swine enzootic pneumonia, porcine pleuropneumonia (Actinobacillus pleuropneumoniae), Aujeszky’s disease, streptococcosis (Streptococcus suis), porcine circovirus infection, foot-and-mouth disease, leptospirosis, transmissible gastroenteritis, cysticercosis (λ = 0.02…0.05). The improvement of the governmental policy for eradication of African swine fever, porcine reproductive and respiratory syndrome, classical swine fever (including the substantial modification of the existing official pig turnover control, zoning, diagnosis and prevention quality, as well as the implementation of biosecurity standards) is the most significant factor, without which the disease eradication perspective is questionable.